De profundis - Wilde, Oscar, 1854-1900 (Biblioteca de ensayo (Madrid, Spain) Serie menor, 2010)
While imprisoned, Wilde wrote this long letter of recrimination to his lover, Lord Alfred Douglas. It offers fascinating insights into Wilde's life in prison and the background and psychology of a notorious affair.